OPTIMASI PEMASANGAN KAPASITOR PADA SISTEM JARINGAN LISTRIK DISTRIBUSI DI BALI MENGGUNAKAN METODE QUANTUM GENETIC ALGORITHM - Agung Ayu Permata, Maria Gusti; Ibi Weking, Antonius; Setiawan, Widyadi (Jurnal SPEKTRUM, 2019)
This study optimized the installation of capacitors on the distribution grid system in Penyabangan feeder, Singaraja, Bali using the Quantum Genetic Algorithm method to reduce the impact of increasing reactive currents. This feeder, consisting of 162 buses in which 62 buses are directly connected to the load and 5 buses are connected to medium voltage cosumers. The results of this study are obtained by the capacity of capacitors installed in 31 buses that have a power factor value less than the permitted limit and the power loss values decrease from 0,0674 MW and 0,0546 MVAr to 0,0543 MW and 0,0442 MVAr.